Pengaruh Disiplin Kerja dan Manajemen Waktu Pengelola Berbasis Gender terhadap Stabilitas Pendapatan pada Toko Dream Shop di Tasikmalaya - Ade Sunita; Marliana B. Winarti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The revenue stability of micro-retail businesses relies heavily on the effectiveness of the manager's internal governance. This stability is influenced by the manager's discipline in adhering to work procedures and the optimality of time management practices amidst the dynamics of gender-based workloads. Dream Shop needs to optimize these two factors to maintain consistent daily revenue. Therefore, this study aims to analyze the impact of these factors on revenue stability at Dream Shop. This study aims to determine the extent to which the manager's work discipline and gender-based time management influence revenue stability at Dream Shop in Tasikmalaya. A descriptive-verificative method with a quantitative approach was employed. Data collection involved distributing questionnaires to the manager and reviewing daily turnover records. The study population consisted of 90 operational days at Dream Shop (covering the period from March to May 2026). A saturation sampling technique was used, involving the entire population as the sample, as they were deemed to possess the most comprehensive understanding of the information required regarding the research subject. Data analysis included validity, reliability, normality, correlation, multiple linear regression, determination, and hypothesis testing, all conducted using the SPSS software application. The results indicate a positive and significant influence of the manager's work discipline and gender-based time management on revenue stability at Dream Shop.